Dynamics of the urinary microbiome in pregnancy and the coincidental predictive value of the microbiota for IVF/IVF–ICSI outcome. Issue 5 (November 2021) - Koedooder, Rivka; Maghdid, Delshad M.; Beckers, Nicole G.M.; Schoenmakers, Sam; Kok, Dik J.; Laven, Joop S.E.
Abstract: Research question: What is the impact of clinical pregnancy on the composition of the urinary microbiota? Design: Eighty-five women receiving IVF, without or with intracytoplasmic sperm injection (ICSI) treatment were enrolled in a prospective observational study performed in 2008. Approximately 14 weeks before the start of hormonal treatment and embryo transfer, a midstream urine sample was obtained, followed by an additional sample 16 weeks after embryo transfer. The microbial composition was determined by polymerase chain reaction of the V1–V3 regions of the 16S rRNA bacterial gene. Clinical pregnancy data were collected after the first IVF/IVF–ICSI cycle and 1 year later. Results: A significant decrease in the abundance of Lactobacillus species as well as a significant increase in that of Staphylococcus species was observed in women who became pregnant after IVF/IVF–ICSI treatment (both P  < 0.0001). In addition, based on the composition of the pretreatment microbiome it was possible to identify women with a lower likelihood of achieving clinical pregnancy after IVF/IVF–ICSI treatment. The resulting prediction model was validated in another 27 women who did not become pregnant during the first cycle and received additional IVF/IVF–ICSI cycle(s) or frozen embryo transfer(s). The model predicted the women with no clinical pregnancy after IVF/IVF–ICSI treatment with a sensitivity of 0.42 and a specificity of 1.00. Conclusions: The data primarily showed that clinical pregnancy results in significant changes in the abundance and diversity of the urinary microbiota. Coincidentally, it was discovered that the urinary microbiome composition before IVF/IVF–ICSI treatment can potentially be used as a predictor of clinical pregnancy.